Planarians (Platyhelminthes)—An Emerging Model Organism for Investigating Innate Immune Mechanisms - Kangale, Luis Johnson; Raoult, Didier; Fournier, Pierre-Edouard; Abnave, Prasad; Ghigo, Eric (Frontiers in Cellular and Infection Microbiology, 2021)
An organism responds to the invading pathogens such as bacteria, viruses, protozoans, and fungi by engaging innate and adaptive immune system, which functions by activating various signal transduction pathways. As invertebrate organisms (such as sponges, worms, cnidarians, molluscs, crustaceans, insects, and echinoderms) are devoid of an adaptive immune system, and their defense mechanisms solely rely on innate immune system components. Investigating the immune response in such organisms helps to elucidate the immune mechanisms that vertebrates have inherited or evolved from invertebrates. Planarians are non-parasitic invertebrates from the phylum Platyhelminthes and are being investigated for several decades for understanding the whole-body regeneration process. However, recent findings have emerged planarians as a useful model for studying innate immunity as they are resistant to a broad spectrum of bacteria. This review intends to highlight the research findings on various antimicrobial resistance genes, signaling pathways involved in innate immune recognition, immune-related memory and immune cells in planarian flatworms.